SOCIAL PROBLEMS OF LABOR - Rakhmatov Nuriddin Negkadamovich (Modern American Journals, 2025)
As is known, labor is a conscious and physical activity aimed at a person's social life. Due to labor, a person achieves social, physiological and spiritual perfection, and by working on himself, he acquires the key to great success. The article considers that as a result of economic, social, and political reforms in Uzbekistan, theoretical and practical ideas about labor have changed in the thinking of scientists and people, and attention to human labor has become an important economic and social category. Labor is a great force and opportunity in human life, and it has the potential to solve many problems and issues. In addition, by solving the social problems of labor, it is possible to ensure human perfection, achieve high efficiency, and bring great benefits to society.
Keywords: Economic, social, political reforms, man, labor, relations, socio-economic thinking.